Concordance in the Mental Health of Spouses: Analysis of a Large National Household Panel Survey - Rodgers, B; Butterworth, P (My University, 2006)
Background. Spousal concordance for common mental disorders provides evidence of the relevance of social contextual factors. There are, however, limitations within the existing literature examining spousal similarity in mental health and little consensus as to the causes of spousal similarity. This study considers a large representative sample and examines an extensive range of risk factors using multilevel statistical methods to explore spousal similarity in common mental disorders. Method. Data were from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, a large nationally representative survey of Australian households. Analysis focused on 3808 mixed-sex couples in marriage and de facto relationships. Multilevel models assessed the mental health scale of the SF-36. Analyses considered risk factors at the individual, couple and area levels, examined the effects of relationship duration on concordance, and considered longitudinal data to assess the consistency with cross-sectional analysis. Results. Significant spousal concordance on the mental health scale was demonstrated (r=0·25) and was independent of, and unexplained by mental health risk factors, including experience of multiple shared life events. Spousal similarity for mental health increased across the first 5 years of relationships. Conclusions. Evidence of spousal concordance for common mental disorders highlights the importance of the social context of marriage in the aetiology of mental illness and identifies an important direction for further research.
Psychological Medicine
Keywords: Health -- Mental; Relationships; Health; Relationships -- Spouse; Health and wellbeing; Health; Relationships; Spouse; Mental; Health and wellbeing